2022
DOI: 10.1530/eje-21-0897
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and genetic heterogeneity of HNF4A/HNF1A mutations in a multicentre paediatric cohort with hyperinsulinaemic hypoglycaemia

Abstract: Objective The phenotype mediated by HNF4A/HNF1A mutations is variable and includes diazoxide-responsive hyperinsulinaemic hypoglycaemia (HH) and maturity-onset diabetes of the young (MODY). Design We characterised an international multi-centre paediatric cohort of patients with HNF4A or HNF1A mutations presenting with HH over a 25-year period (1995-2020). Methods Clinical and genetic analysis data from five centres were obtained. Diazoxide-responsiveness was defined as the ability to maintain normoglyca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Furthermore, HNF1A is involved in maintaining the stability and lineage commitment of hepatocytes, suppressing their plasticity and preventing lineage switching. Dysregulated expression of HNF1A in HCC may disrupt this regulatory function, leading to enhanced cellular plasticity and an increased propensity for transdifferentiation [51]. HCC cells with dysregulated HNF1A expression may exhibit greater exibility in adopting alternative cell fates, such as acquiring features of pancreatic β-cells, intestinal epithelial cells, or other cell types where HNF1A is involved.…”
Section: Dysregulated Expression In the Emergence Of Transdifferentia...mentioning
confidence: 99%
“…Furthermore, HNF1A is involved in maintaining the stability and lineage commitment of hepatocytes, suppressing their plasticity and preventing lineage switching. Dysregulated expression of HNF1A in HCC may disrupt this regulatory function, leading to enhanced cellular plasticity and an increased propensity for transdifferentiation [51]. HCC cells with dysregulated HNF1A expression may exhibit greater exibility in adopting alternative cell fates, such as acquiring features of pancreatic β-cells, intestinal epithelial cells, or other cell types where HNF1A is involved.…”
Section: Dysregulated Expression In the Emergence Of Transdifferentia...mentioning
confidence: 99%
“…One centre reported that HNF4A mutations are the third most common cause of diazoxide-responsive CHI accounting for 18.6% of cases with identifiable genetic aetiology ( Flanagan et al, 2010 ). CHI generally develops within the first week of life with the majority presenting within the first two days of life ( Flanagan et al, 2010 ; Tung et al, 2018 ; McGlacken-Byrne et al, 2022 ). Inactivating HNF4A mutations associated with CHI tend to arise from the 7–9 isoforms expressed in the P2 promotor ( Kapoor et al, 2008 ).…”
Section: Hnf4a-modymentioning
confidence: 99%
“…Increased expression levels of the DNM1L proteins may correlate with the degree of weight gain, and is closely related to the development of obesity (49)(50)(51)(52). HNF4A mutations are associated with a considerable increase in birth weight and macrosomia, and the gene acts in the intestine and kidney to promote white adipose tissue energy storage (53)(54)(55)(56). MKX is a potential regulator of brown adipose tissue development associated with obesity-related metabolic dysfunction in children (57).…”
Section: Snpmentioning
confidence: 99%